Electronic Health Record Dalam Pelaksanaan Handover Keperawatan Di Rumah Sakit Jakarta - Wulandari, Cicilia Ika; Ardianti, Sumiati Devi; Pasaribu, Jesika (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
ABSTRACT Background: Electronic health record is an electronic record of health-related information that includes patient information such as biodata, medical history, allergy history, test results, and all important care information used in the implementation of Nursing Handover. Objective: This study aims to find out more about the experience of nurses in applying electronic health records during handovers in hospitals. Design: This study uses a qualitative method with a phenomenological approach using the colaizzi method. Sampling using purposive sampling with the number of participants 8 people. Data collection by means of focus group discussions. Results: This study resulted in four main themes: (1) Nurses' understanding of handovers using an electronic format, (2) Advantages of using electronic health records, namely convenience, clarity, security and minimizing errors, (3) Negative and positive experiences of using electronic health records ( 4) Electronic health record constraints in handover. Conclusion: The use of electronic health record applications at the time of handover can minimize communication errors and can improve patient safety in hospitals. Keywords: Electronic Health Records; Handovers; Nurse; Qualitative